Expression Analysis of Sugarcane Aquaporin Genes under Water Deficit - Manassés Daniel da Silva; Roberta Lane de Oliveira Silva; José Ribamar Costa Ferreira Neto; Ana Carolina Ribeiro Guimarães; Daniela Truffi Veiga; Sabrina Moutinho Chabregas; William Lee Burnquist; Günter Kahl; Ana Maria Benko-Iseppon; Ederson Akio Kido (Journal of Nucleic Acids)
The present work is a pioneer study specifically addressing the aquaporin transcripts in sugarcane transcriptomes. Representatives of the four aquaporin subfamilies (PIP, TIP, SIP, and NIP), already described for higher plants, were identified. Forty-two distinct aquaporin isoforms were expressed in four HT-SuperSAGE libraries from sugarcane roots of drought-tolerant and -sensitive genotypes, respectively. At least 10 different potential aquaporin isoform targets and their respective unitags were considered to be promising for future studies and especially for the development of molecular markers for plant breeding. From those 10 isoforms, four (SoPIP2-4, SoPIP2-6, OsPIP2-4, and SsPIP1-1) showed distinct responses towards drought, with divergent expressions between the bulks from tolerant and sensitive genotypes, when they were compared under normal and stress conditions. Two targets (SsPIP1-1 and SoPIP1-3/PIP1-4) were selected for validation via RT-qPCR and their expression patterns as detected by HT-SuperSAGE were confirmed. The employed validation strategy revealed that different genotypes share the same tolerant or sensitive phenotype, respectively, but may use different routes for stress acclimation, indicating the aquaporin transcription in sugarcane to be potentially genotype-specific.